Epidemiology of Plasmodium vivax malaria in Peru - Rosas-Aguirre A. (2016)
Malaria in Peru, dominated by Plasmodium vivax, remains a public health problem. The 1990s saw newly epidemic malaria emerge, primarily in the Loreto Department in the Amazon region, including areas near to Iquitos, the capital city, but sporadic malaria transmission also occurred in the 1990s-2000s in both north-coastal Peru and the gold mining regions of southeastern Peru. Although a Global Fund-supported intervention (PAMAFRO, 2005-2010) was temporally associated with a decrease of malaria transmission, from 2012 to the present, both P. Vivax and Plasmodium falciparum malaria cases have rapidly increased. The Peruvian Ministry of Health continues to provide artemesininbased combination therapy for microscopy-confirmed cases of P. Falciparum and chloroquine-primaquine for P. Vivax. Malaria transmission continues in remote areas nonetheless, where the mobility of humans and parasites facilitates continued reintroduction outside of ongoing surveillance activities, which is critical to address for future malaria control and elimination efforts. Ongoing P. Vivax research gaps in Peru include the following: identification of asymptomatic parasitemics, quantification of the contribution of patent and subpatent parasitemics to mosquito transmission, diagnosis of nonparasitemic hypnozoite carriers, and implementation of surveillance for potential emergence of chloroquine- and 8-aminoquinoline-resistant P. Vivax. Clinical trials of tafenoquine in Peru have been promising, and glucose-6-phosphate dehydrogenase deficiency in the region has not been observed to be a limitation to its use. Larger-scale challenges for P. Vivax (and malaria in general) in Peru include logistical difficulties in accessing remote riverine populations, consequences of government policy and poverty trends, and obtaining international funding for malaria control and elimination. Copyright © 2016 by The American Society of Tropical Medicine and Hygiene.